(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Low backache is commonly experienced by adults at some time during their lives. Though it is caused by degenerative changes, spinal stenosis, neoplasm, infection and trauma, lumbar disc degeneration is the most commonly diagnosed abnormalities associated. As Magnetic Resonance Imaging (MRI) is non invasive imaging technique with excellent spatial and contrast resolution, it has become the investigation of choice in evaluation of patients with low back pain. This study was designed to determine the patterns of degenerative disc disease on MRI in patients with low backache. Methods: A retrospective hospital based study was done by reviewing MRI report of 202 patients who underwent MRI of lumbar spine for complaint of chronic low back pain, radicular pain, neurogenic claudication or various other symptoms and signs suggestive of lumbar degenerative disc disease from January 2014 till June 2014. The patients having MRI findings of acute spinal infection, recent trauma, tumors, spinal dysraphism and metabolic conditions were excluded from the study. Results: Out of the 202 patients included in the study, 116 patients (57.4%) were male and 86 patients (42.6%) were female. The mean age of the study population was 44.26 ±15.61 (13-83) years. Multiple contiguous level disc disease was the most common type of involvement which was noted in 109 (54%) patients. Grade 4 lumbar disc degeneration (graded as per classification given by Pfirrmann et al) was noted in 65.3% (132) cases followed by Grade 2 in 25.2%(51) cases and Grade 1in 5.5% (11) cases. The most common involvement was observed at L4-L5 level (76.7%) and L5-S1 levels (55.9%) followed by L3-L4 (30.6%) in decreasing order of frequency. The most common category was disc bulge note in 46.5% (94) of cases. Nerve root compression was observed in 56% (114) of the total cases. Nerve root compromise was also noted most frequently compressing L5 nerve (28.23% of cases). Annular tear was observed in 14.4% (29) of cases and among them 20% (6) of cases had torn at two intervertebral discs. It is most frequently noted involving L4-L5 intervertebral disc (72.5% of cases), followed by L5-S1 (24.2% of cases). Conclusion: Disc generation is most common at L4-L5 level with multiple contiguous involvement of grade 4. Annular tear though not common can occur and is also common at L4-L5 level. Journal of Society of Surgeons of Nepal, 2015; 18 (2)